2024
DOI: 10.1002/oby.23986
|View full text |Cite
|
Sign up to set email alerts
|

The associations of “weekend warrior” and regularly active physical activity with abdominal and general adiposity in US adults

Lubi Lei,
Jingkuo Li,
Wei Wang
et al.

Abstract: ObjectiveThis study examined the association between physical activity patterns and abdominal and general adiposity.MethodsData were extracted among 20‐ to 59‐year‐old participants in the National Health and Nutrition Examination Survey (NHANES) from 2011 to 2018. Abdominal and general adiposity was assessed by dual‐energy x‐ray absorptiometry (DXA) and anthropometric measures. DXA‐measured indicators were further normalized into z scores. Physical activity levels were collected by questionnaire and classified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…This method is adapted to accurately capture instances of moderate (MPA) and vigorous (VPA) physical activities that last for a minimum of 10 continuous minutes. We calculated weekly leisure-time PA by aggregating the total minutes engaged in MPA and VPA, adjusting for intensity differences by equating 1 min of VPA to 2 min of MPA (Piercy et al, 2018 ; Lei et al, 2024 ). Furthermore, PA was analyzed both as a continuous variable and categorical variable.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method is adapted to accurately capture instances of moderate (MPA) and vigorous (VPA) physical activities that last for a minimum of 10 continuous minutes. We calculated weekly leisure-time PA by aggregating the total minutes engaged in MPA and VPA, adjusting for intensity differences by equating 1 min of VPA to 2 min of MPA (Piercy et al, 2018 ; Lei et al, 2024 ). Furthermore, PA was analyzed both as a continuous variable and categorical variable.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, PA was analyzed both as a continuous variable and categorical variable. We differentiated total PA into three primary patterns: “Inactive” for those accumulating < 150 min of total PA per week (Bull et al, 2020 ); WW for individuals meeting or exceeding 150 min of total PA weekly within one or two sessions; and RE for those distributing the same or greater amount of PA across more than two sessions weekly (Lei et al, 2024 ). Additionally, we introduced a refined classification to assess PA intensity more precisely, segmenting it into four categories: “MPA-Total” where all activity is of moderate intensity, “MPA-dominated” for activities predominantly of moderate intensity but including some vigorous activity, “VPA-dominated” where vigorous activity exceeds moderate intensity, and “VPA-Total” for exclusively vigorous activity.…”
Section: Methodsmentioning
confidence: 99%
“…To quantify PA, we adopted methodologies consistent with those utilized in prior research, treating PA both as a continuous variable for analytical purposes and as a categorical variable for ease of interpretation and application to public health guidelines ( You et al, 2023 ; Lei et al, 2024 ; Wang N, et al, 2024 ). The categorization of PA levels was grounded in the recommendations set forth by the United States Physical Activity Guidelines ( Health USDo, 2008 ).…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that concentrating on physical activity 1 or 2 days per week (WW model) versus an average weekly schedule of physical activity (RA model) are both associated with lower DXA measures of fat mass (both in the abdominal region and whole body), BMI, and waist circumference. The WW model may also be applicable to the prevention of NAFLD ( 92 ).…”
Section: Lifestyle Interventions Of Mafldmentioning
confidence: 99%